2022
DOI: 10.3389/fvets.2022.872205
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the NSP9 Protein of Porcine Reproductive and Respiratory Syndrome Virus

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is a contagious disease caused by the porcine reproductive and respiratory syndrome virus (PRRSV). PRRS is also called “blue ear disease” because of the characteristic blue ear in infected sows and piglets. Its main clinical features are reproductive disorders of sows, breathing difficulties in piglets, and fattening in pigs, which cause considerable losses to the swine industry. NSP9, a non-structural protein of PRRSV, plays a vital role in PRRSV replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Porcine reproductive and respiratory syndrome virus (PRRSV) can cause fever and anorexia in infected pigs, late abortion, premature delivery, stillbirth, weak and mummified fetuses in pregnant sows, and death of pigs of all ages (mainly piglets) because of respiratory diseases [ 1 ]. Infection with highly pathogenic strains can cause fever, skin cyanosis, dyspnea, and acute death in adult pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Porcine reproductive and respiratory syndrome virus (PRRSV) can cause fever and anorexia in infected pigs, late abortion, premature delivery, stillbirth, weak and mummified fetuses in pregnant sows, and death of pigs of all ages (mainly piglets) because of respiratory diseases [ 1 ]. Infection with highly pathogenic strains can cause fever, skin cyanosis, dyspnea, and acute death in adult pigs.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative explanation is that ZnO–Se NPs could impact the process of PRRSV replication by interfering with the proteins involved in PRRSV replication within host cells. Nonstructural protein 9 (Nsp9), functioning as a RNA-dependent RNA polymerase (RdRp), is crucial for genome replication and subgenomic (sg mRNA) synthesis and plays a pivotal role in viral replication . It has been previously reported that some host proteins such as Annexin A2 (ANXA2), DEAD-box RNA helicase 5 (DDX5), retinoblastoma protein (pRb), and nucleotide-binding oligomerization domain-like receptor X1 (NLRX1) can bind Nsp9 to regulate replication of PRRSV.…”
Section: Resultsmentioning
confidence: 99%
“…Nonstructural protein 9 (Nsp9), functioning as a RNA-dependent RNA polymerase (RdRp), is crucial for genome replication and subgenomic (sg mRNA) synthesis and plays a pivotal role in viral replication. 44 It has been previously reported that some host proteins such as Annexin A2 (ANXA2), 45 DEAD-box RNA helicase 5 (DDX5), 46 retinoblastoma protein (pRb), 47 and nucleotidebinding oligomerization domain-like receptor X1 (NLRX1) 48 can bind Nsp9 to regulate replication of PRRSV. Therefore, the expression of some host proteins that can interact with Nsp9 was examined by RT-qPCR.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations